1991
DOI: 10.1073/pnas.88.23.10629
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression cloning and characterization of the hepatocyte Na+/bile acid cotransport system.

Abstract: Liver parenchymal cells continuously extract high amounts of bile acids from portal blood plasma. This uptake process is mediated by a Na+/bile acid cotransport system. A cDNA encoding the rat liver bile acid uptake system has been isolated by expression cloning in Xenopus laevis oocytes. The cloned transporter is strictly sodium-dependent and can be inhibited by various non-bile-acid organic compounds. Sequence analysis of the cDNA revealed an open reading frame of 1086 nucleotides coding for a protein of 362… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
284
2
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 431 publications
(294 citation statements)
references
References 36 publications
6
284
2
2
Order By: Relevance
“…The bile acid transporters NTCP (SLC10A1) and ASBT (SLC10A2) NTCP As the first member of the SLC10 family, the Na + / taurocholate cotransporting polypeptide (Ntcp; Slc10a1) was isolated from rat liver mRNA by expression cloning using the Xenopus laevis oocytes expression system (Hagenbuch et al 1990(Hagenbuch et al , 1991. Further orthologs were subsequently cloned from human , mouse (Cattori et al 1999) and rabbit livers.…”
Section: Functional Properties and Expression Patterns Of The Individmentioning
confidence: 99%
See 2 more Smart Citations
“…The bile acid transporters NTCP (SLC10A1) and ASBT (SLC10A2) NTCP As the first member of the SLC10 family, the Na + / taurocholate cotransporting polypeptide (Ntcp; Slc10a1) was isolated from rat liver mRNA by expression cloning using the Xenopus laevis oocytes expression system (Hagenbuch et al 1990(Hagenbuch et al , 1991. Further orthologs were subsequently cloned from human , mouse (Cattori et al 1999) and rabbit livers.…”
Section: Functional Properties and Expression Patterns Of The Individmentioning
confidence: 99%
“…Membrane insertion and sorting of NTCP and ASBT Based on bioinformatic predictions and experimental data, it has been shown that NTCP and ASBT have an extracellular N-terminus, an odd number of transmembrane helices (seven or nine) and a cytoplasmic Cterminus (Hagenbuch et al 1991;Hagenbuch and Meier 1994;Stieger et al 1994;Dawson and Oelkers 1995;Hallén et al 1999;Hallén et al 2002b;Zhang et al 2004). Several potential N-glycosylation sites are present in NTCP, ASBT and SOAT proteins, and site-directed mutagenesis has revealed that only N 5 and N 11 in rat Ntcp (Hagenbuch 1997), and N 10 in human ASBT (Zhang et al 2004) are glycosylated.…”
Section: Functional Properties and Expression Patterns Of The Individmentioning
confidence: 99%
See 1 more Smart Citation
“…Structurally speaking, NTCP is a 55‐kDa N‐glycosylated multipass transmembrane protein composed of 349 amino acids that shares over 70% sequence similarity with rat Ntcp 14, 15. On the N‐terminal domain, two N‐linked glycosylation sites (Asn 5, Asn 11) facing the extracellular lumen have been characterized15, 16 and are important for NTCP localization on the plasma membrane 17.…”
mentioning
confidence: 99%
“…On the N‐terminal domain, two N‐linked glycosylation sites (Asn 5, Asn 11) facing the extracellular lumen have been characterized15, 16 and are important for NTCP localization on the plasma membrane 17. Current knowledge of NTCP ontogenesis is mostly based on experiments conducted on rats and shows that i) compared to adult levels, Ntcp messenger RNA (mRNA) levels at birth are 35%‐76%; ii) in newborns, Ntcp protein expression reaches adult levels during the first postnatal week; iii) Ntcp expression levels and plasma membrane localization do not correlate with protein functional status; iv) NTCP activity is delayed approximately 4 weeks after birth 6, 18, 19, 20, 21.…”
mentioning
confidence: 99%